An empirical examination of currency ETFs tracking error. (2015) - Ivanov, Stoyu I.
In this paper, I study on intradaily basis six currency ETFs' tracking error volatility around the Great Recession - 12/30/2002 to 04/05/2013. I study the Australian Dollar ETF (FXA), the British Pound ETF (FXB), the Canadian Dollar ETF (FXC), the Euro ETF (FXE), the Swiss Franc ETF (FXF) and the Japanese Yen ETF (FXY). I find that the FXA, FXB and FXE tracking errors are non-stationary, whereas FXC, FXF and FXY tracking errors are stationary. The FXC, FXF and FXY ETFs tracking errors which are stationary and do not exhibit clustering of volatility are best described by a simple AR(1) model specification. The FXA, FXB and FXE ETFs tracking errors which are non-stationary and exhibit ARCH effects are best described by a AR(1)-GARCH(1, 1) model. An arbitrageur can use these models to forecast these six currency ETFs tracking errors and identify a signal for an arbitrage opportunity.